State of the Art Geo-Energy Technology in China (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dear colleagues, Geological energy has a long history in China. As early as 500 BC, China began to use coal as fuel. In the middle of the 19th century, China began to develop oil resources. After the foundation of new China, with the discovery of the Daqing oilfield, China's oil industry entered an era of great development. During the 21st century, with the development of drilling technology, the development of unconventional energy such as shale gas and shale oil has entered a new era. In recent years, the development of flammable ice has set off a wave of clean energy. With the carbon reduction plan proposed by the Chinese government, clean geo-energy has been granted unparalleled development space in the future. China's geo-energy development technology used to lag behind that of major developed countries for a long time, but after years of development, it has become the world's leading edge in some fields. Therefore, we specially set up this collection to collect China's advanced geo-energy exploitation technology and development trends, whilst providing some new directions for thinking about geo-energy development in China and even the world. This collection seeks to contribute to such topics through enhanced scientific and multidisciplinary knowledge.